Xiaoxuming decoction cutting formula reduces LPS-stimulated inflammation in BV-2 cells by regulating miR-9-5p in microglia exosomes - Wang, Menglei; Yang, Yuting; Guo, Yanlei; Tan, Ruirong; Sheng, Yanmei; Chui, Huawei; Chen, Ping; Luo, Hua; Ying, Zhujun; Li, Li; Zeng, Jin; Zhao, Junning (Frontiers in Pharmacology, 2023)
Stroke is a syndrome of focal damage to the brain caused by various vascular diseases and is the second leading cause of death after malignant tumours. The role of inflammatory mechanisms in stroke related brain injury and post-ischaemic tissue damage is crucial. Xiaoxuming decoction (XXMD) was the first formula for the treatment of stroke in a broad sense during the Tang and Song dynasties in China, and has a very important place in the history of stroke treatment. A review of the famous ancient medical cases of XXMD and modern clinical evidence shows that XXMD is effective in the treatment of stroke and its sequelae, and that its pharmacological mechanism of action may be related to post-stroke inflammation. However, there are 12 herbs in the XXMD formula, which has a complex composition. In this study, the XXMD herbs were reduced based on their anti-inflammatory effects to obtain a simpler formula of Xiaoxuming decoction cutting formula (XXMD-C). Therefore, it is essential to explore and confirm the anti-inflammatory mechanism of XXMD-C.